Clinical and functional characteristics of pseudophakic myopia in children after congenital cataract extraction in infancy - L. A. Katargina; T. B. Kruglova; A. S. Mamykina; N. S. Egiyan; N. N. Arestova (Российский офтальмологический журнал)
One of the serious challenges facing surgeons after congenital cataract extraction with IOL implantation in infancy is unplanned refractive results revealed in the long-term period, including the cases of myopia higher than 3.0 D in approximately 50 %.   Purpose. The study aimed to evaluate the clinical and functional condition of the eyes in children with moderate to high myopia.   Material and methods. Our study included a total of 33 patients (61 eyes) with pseudophakia, of which 16 (26 eyes) developed moderate (12 eyes) or high (14 eyes) myopia at the age of 5 to 15 years. Parameters of the anterior and posterior eye segments were evaluated using Galilei Dual Scheimpflug Analyzer and Optical Coherence Tomography RS-3000 Advance 2, and the axial length using Optical Biometer Al-Scan.   Results. The central corneal thickness (CCT) was found considerably above the norm (up to 580 ± 35 pm) in most cases of pseudophakic myopia (72.2 %). Anterior chamber depth in children (4.07 ± 0.39 mm) was equal to that in adults with pseudophakia. Astigmatism and axial length in children with highmyopia significantly exceeded those in children with moderate myopia (3.5 and 1.88 D; 23.57 ± 1.31 and 25.04 ± 1.90 mm, respectively), while choroidal thickness and best corrected visual acuity (BCVA) were much lower (268 and 181 pm; 0.1 and 0.3, respectively). There were no variations in spherical equivalent between different axial length in high and moderate myopia.   Conclusion. Taken together these results suggest that with the increase of astigmatism axial length elongated and high myopia developed in children with pseudophakia. Choroidal thickness declined due this process and may be a cause of poor functional outcome. Sufficient CCT opens possibilities for refractive surgery in those patients to improve visual outcomes.